Alteration of sphingolipid metabolism as a putative mechanism underlying LPS‐induced BBB disruption. Issue 2 (28th December 2017) - Vutukuri, Rajkumar; Brunkhorst, Robert; Kestner, Roxane‐Isabelle; Hansen, Lena; Bouzas, Nerea Ferreiros; Pfeilschifter, Josef; Devraj, Kavi; Pfeilschifter, Waltraud
Abstract: Septic encephalopathy with confusion and agitation occurs early during sepsis and contributes to the severity of the disease. A decrease in the sphingosine‐1‐phosphate (S1P) blood levels has been shown in patients and in animal models of sepsis. The lipid mediator S1P is known to be involved in endothelial barrier function in a context‐dependent manner. We utilized lipopolysaccharide (LPS)‐injected mice as a model for septic encephalopathy and first performed tracer permeability assays to assess the blood–brain barrier (BBB) breakdown in vivo. At time points corresponding to the BBB breakdown post LPS injection, we aimed to characterize the regulation of the sphingolipid signaling pathway at the BBB during sepsis. We measured sphingolipid concentrations in blood, in mouse brain microvessels (MBMVs), and brain tissue. We also analyzed the expression of S1P receptors, transporters, and metabolizing enzymes in MBMVs and brain tissue. Primary mouse brain microvascular endothelial cells (MBMECs) were isolated to evaluate the effects of LPS on transendothelial electrical resistance (TEER) as a measure of permeability in vitro . We observed a relevant decrease in S1P levels after LPS injection in all three compartments (blood, MBMVs, brain tissue) that was accompanied by an increased expression of the S1P receptor type 1 and of sphingosine kinase 1 on one hand and of the S1P degrading enzymes lipid phosphate phosphatase 1 (LPP1) and S1P phosphatase 1 on the other hand, as well as a down‐regulation of sphingosine kinase 2. Application of LPS to a monolayer of primary MBMECs did not alter TEER, but serum from LPS‐treated mice lead to a breakdown of the barrier compared to serum from vehicle‐treated mice. We observed profound alterations of the sphingolipid metabolism at the BBB after LPS injection that point toward a therapeutic potential of drugs interfering with this pathway as novel approach for the detrimental overwhelming immune response in sepsis. Read the Editorial Highlight for this article on page 115 . Cover Image for this Issue: doi.10.1111/jnc.14161 . Abstract : Sphingosine‐1‐phosphate (S1P) is a versatile signaling molecule that has been shown to modulate endothelial barrier function. We found a significant decrease in S1P concentrations in serum, whole brain homogenates, and brain microvessels after LPS injection as a model for sepsis entraining septic encephalopathy and brain edema concentrations in serum that correlates with a down‐regulation of sphingosine kinase 2 (SphK2) expression and putatively compensatory changes of SphK1 and S1P receptor S1PR1. Read the Editorial Highlight for this article on page 115 . Cover Image for this Issue: doi.10.1111/jnc.14161 .